Hybrid nanomanufacturing of mixed-dimensional manganese oxide/graphene aerogel macroporous hierarchy for ultralight efficient supercapacitor electrodes in self-powered ubiquitous nanosystems. (December 2019) - Ma, Chenxiang; Wang, Ruoxing; Tetik, Halil; Gao, Shengjie; Wu, Min; Tang, Zhiyuan; Lin, Dong; Ding, Dong; Wu, Wenzhuo
Abstract: The economic production of wearable energy storage devices exhibiting mechanically-compliable form factors and reliable performance enable exciting opportunities in emerging technologies of consumer electronics, human-machine interface, and the Internet of Things. Here we report a hybrid scheme for designing and nanomanufacturing ultralight, high-performance supercapacitor electrodes through the hydrothermal growth of two-dimensional MnO2 on three-dimensional printed graphene aerogel (GA). The derived mixed-dimensional hierarchical macroporous composite electrodes exhibit superior specific capacitance and excellent cycling stability after thousands of cycles. We further explored the integration of a contact mode triboelectric nanogenerator and a mixed-dimensional MnO2 /GA based supercapacitor into a self-powered system that is capable of converting mechanical signals into electrical power and further storing such scavenged power. The holistic integration of energy harvesting and storage units promises the implementation of self-powered wearable devices with greater intelligence that can scavenge and store environmental energy through sustainable pathways for ubiquitous electronics in societally-pervasive applications. Graphical abstract: The mixed-dimensional macroporous ultralight supercapacitor electrodes for self-powered ubiquitous nanosystems. Image 1 Highlights: An ultralight supercapacitor electrode was nanomanufactured via growing MnO2 nanosheets on 3-D printed graphene aerogel. The MnO2 /GA electrodes exhibit superior specific capacitance and excellent cycling stability. An integrated self-powered nanosystem was demonstrated.